Synthesis, Cyclic Voltammetry and Photophysical Properties of a Bridged o-Phenylenediamine C-60 Dyad. - Diekers, Michael; Hirsch, Andreas; Luo, Chuping; Guldi, Dirk Michael; Bauer, Klaus Andreas; Nickel, Ulrich (Organic Letters, 2000)
The synthesis, complete spectroscopic characterization, cyclic voltammetry, and photophysical measurements of a new o-phenylenediamine-C dyad are described. By using a tether strategy, only a single regioisomer was obtained. Cyclic voltammetry measurements indicate that the two electroactive groups do not interact in their singlet ground states. Photophysical investigations reveal a rapid photoinduced electron transfer between the singlet excited state of the fullerene acceptor and the o-phenylenediamine donor, yielding a charge-separated radical pair.
UnivIS-Import:2015-03-06:Pub.2000.nat.dchph.ppc25.synthe